IMPROVEMENT OF ENTREPRENEURSHIP THROUGH STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND KNOWLEDGE MANAGEMENT - Yusnita, Nancy; Virlania, Yusi (jfpublisher, 2024)
The increasing number of unemployed in Indonesia, which is caused by an imbalance between the number of the workforce and employment opportunities, is one of the reasons why entrepreneurs are needed. The aim of this research is to find efforts to increase entrepreneurship in teachers of Private Vocational High Schools in North Bogor, Bogor through strengthening transformational leadership and knowledge management, by identify and analyze the influence between these variables. This research was conducted on 121 teachers in North Bogor, Bogor to ensure improved Entrepreneurship by concerning at the strengthening transformational leadership, knowledge management. It uses a quantitative survey-by-survey approach using path analysis. Regression analysis with a significance level = 0.05 was used to test the hypothesis. Based on the research results it can be assumed that entrepreneurship can be further developed by strengthening transformational leadership and knowledge management, both exclusively and as a whole.